1989
DOI: 10.1530/acta.0.1210168
|View full text |Cite
|
Sign up to set email alerts
|

Serum thyroglobulin during the menstrual cycle, during pregnancy, and post partum

Abstract: Serum thyroglobulin, TSH, thyroid hormones and thyroid volume were investigated during the menstrual cycle in 10 healthy females (day 2, 9, 16, 23 and day 2 of next cycle), during pregnancy (week 18, 24, 30 and 36) and post partum (1, 2, 3, 6 and 12 months) in 20 healthy females. During the menstrual cycle median serum thyroglobulin increased from 27 (day 2) to 32 \ g=m\ g/ l (day 23, p < 0.01 ). Serum TSH and thyroid volume demonstrated a similar increase with a positive correlation between serum thyroglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 19 publications
3
27
1
Order By: Relevance
“…We also detected no increase in Tg until the third trimester. Increased Tg has been shown by others in relatively iodine deficient women (22,23).…”
Section: Discussionmentioning
confidence: 58%
“…We also detected no increase in Tg until the third trimester. Increased Tg has been shown by others in relatively iodine deficient women (22,23).…”
Section: Discussionmentioning
confidence: 58%
“…In a series of illustrative investigations in Belgium (Glinoer et al, 1990;Glinoer et al, 1995), it was shown that the FT4 levels tend to decrease and the TSH levels to increase, but remain within the reference ranges of non-pregnant individuals. Several reports indicate an increase in thyroid volume during pregnancy (Glinoer et al, 1990;Rasmussen et al, 1989;Glinoer et al, 1995). Precise determinations of thyroid volume need thyroid ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies in the literature reported different results. While some studies showed that TV reached peak at luteal phase during MC (Rasmussen et al 1989;Chan et al 1998), a correlation was also shown between TSH and Tg, and TV (Rasmussen et al 1989). In pregnancy, increases in Tg and TV were demonstrated without any alterations in levels of TSH or thyroid hormones.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it could theoretically be expected that physiological changes in LH and FSH within MC would also occur in TSH, and intra-cycle changes in TSH would lead to alterations in TV and thyroid blood flow. In literature, there are few studies evaluating TV, thyroid functions, and Tg levels during MC (Hegedu¨s et al 1986;Rasmussen et al 1989). Thyroid Doppler parameters were also studied throughout MC (Chan et al 1998(Chan et al , 1999Krezia et al 2004).…”
Section: Discussionmentioning
confidence: 99%